Critical success factors for value management techniques in construction projects: case in Jordan. Issue 4 (12th March 2023) - Thneibat, Mujahed M.; Al-Shattarat, Basiem
Abstract: This study aims to identify the critical success factors (CSFs) of Value Management (VM) in construction projects in the context of developing countries. The article serves as a preliminary study on the status of VM in developing countries. A questionnaire survey and interviews with construction professionals have been conducted to highlight possible success factors to achieve this aim. The 181 returned surveys were analysed using factor analysis to explore the inherent relationships between the highly ranked CSFs. The study reveals that Client Support, Awareness of the VM team, the VM facilitator's proficiency, and the VM team environment are the main clusters that describe the connections between CSFs. Besides the scarcity of VM studies in developing countries, our study provides insights into how VM techniques can be smoothed in construction projects. Additionally, the article introduces two novels CSFs to the field of VM that has not been investigated before.